2013
DOI: 10.1089/dia.2013.0117
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Continuous Subcutaneous Insulin Infusion Therapy in Perioperative Patients with Diabetes Mellitus

Abstract: Background: Hyperglycemia is common and hard to control in surgical patients with diabetes. We retrospectively investigated short-term effects of continuous subcutaneous insulin infusion (CSII) in perioperative patients with diabetes. Patients and Methods: Perioperative patients with diabetes discharged between January 1, 2006 and January 1, 2012 were included. Glucose control and postoperative outcomes were compared between the patients using CSII or non-CSII insulin therapy. Results: We identified 108 pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Several studies have shown that the use of CSII during the perioperative period is safe and effective; it led to better glucose control, shorter anesthesia time, and a lower proportion of general anesthesia recipients. 31,37,38 It is interesting to note that the CSII group had less glucose fluctuation as compared with the MDI group. Several reasons account for this difference.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several studies have shown that the use of CSII during the perioperative period is safe and effective; it led to better glucose control, shorter anesthesia time, and a lower proportion of general anesthesia recipients. 31,37,38 It is interesting to note that the CSII group had less glucose fluctuation as compared with the MDI group. Several reasons account for this difference.…”
Section: Discussionmentioning
confidence: 96%
“…[5][6][7][8][9][10] Furthermore, there is evidence supporting that perioperative hyperglycemia is also associated with a higher rate of hospital complications and mortality. 3,4,13,42 Since our previous work showed the advantage of CSII in perioperative glucose management, 31 it was intriguing to know whether CSII also has positive effects in reducing infection and improving postoperative outcomes. In order to answer this question, the present study collected more cases and had a larger sample size (253 pairs of patients) for a more detailed new analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found insulin pump use in the perioperative setting had no increased medical expenditures and had similar patient outcomes as standard insulin injections [30]. Some protocols recommend reducing the basal insulin by 20% at midnight before surgery when using an insulin pump, but no consensus has been agreed upon [20].…”
Section: Insulin and Oral Hypoglycemic Agentsmentioning
confidence: 99%
“…Emerging data indicate that insulin pumps can be safely allowed in the operating suites and may provide glucose control comparable to intravenous insulin infusions. [2][3][4] Individual institutions are now developing care process models (CPMs) to provide guidance on use of CSII during the perioperative phase of surgical care, 3,5 although some still recommend disconnecting the pump for procedures lasting longer than 3 hours. 6 Despite rising interest in this topic, consensus strategies for maintaining insulin pump systems during surgery continue to lag, and subspecialty organizations and experts remain silent on the topic.…”
mentioning
confidence: 99%